2020
DOI: 10.1016/j.avsg.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of a Ruptured Pararenal Abdominal Aortic Aneurysm in a Patient With Coronavirus Disease-2019: Suggestions and Case Report

Abstract: The aim of this report is to discuss emergent repair for complex aortic diseases in patients affected by novel coronavirus pneumonia (coronavirus disease-2019 ), describing a case of ruptured pararenal aortic aneurysm. An eighty-year-old man with COVID-19 was admitted for ruptured aneurysm of the pararenal aorta and hemorrhagic shock. Endovascular repair was chosen, and a proximal extension of the previous abdominal endograft was performed with parallel stents in the right renal artery and the superior mesente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
0
16
0
1
Order By: Relevance
“…Though there is no known association between COVID-19 and aneurysm formation, there may be accelerated thrombus formation in preexisting aneurysms. At least two cases of aortic aneurysm rupture during active COVID-19 infections have been reported [89,90]. A similar report exists for thrombosis in a popliteal aneurysm [91].…”
Section: Abnormal Blood Flowmentioning
confidence: 58%
“…Though there is no known association between COVID-19 and aneurysm formation, there may be accelerated thrombus formation in preexisting aneurysms. At least two cases of aortic aneurysm rupture during active COVID-19 infections have been reported [89,90]. A similar report exists for thrombosis in a popliteal aneurysm [91].…”
Section: Abnormal Blood Flowmentioning
confidence: 58%
“…The benefits of EVAR/TEVAR during the COVID-19 outbreak have been described. 9,10 Two patients were treated for carotid disease, with conventional patch endarterectomy, and 7 patients for hemodialysis access (fistula creation) by open means as well.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were excluded if they reported tracheostomy outcomes only; did not involve a surgical intervention; the diagnosis of COVID-19 was based on symptoms or X-ray findings only; did not 16 Paris Urology All Yes Di Martino 17 Spain Gen Surg All Yes Alvarez Gallego 18 Spain Gen Surg All Yes Kayani 19 UK Ortho Emergency Yes Egol 20 USA Ortho Emergency Yes Cai 21 China Gen Surg Emergency Yes Javanmard-Emamghissi 22 UK Gen Surg Emergency Yes Barkhordari 23 Iran Cardiac Emergency Yes Sobti 24 UK Trauma/Orthopaedics Emergency Yes COVIDSurg Collaborative 8 Global All All No Dai 25 China Cancer Elective No Lei 26 China All Elective No Shrikhande 27 India Cancers Elective No Aminian 28 Iran Gen Surg Elective No Zhong 29 China Ortho/Gynae Emergency No Munoz Vives 30 Spain Ortho Emergency No Bellosta 31 Italy Vascular Emergency No Chen 32 China Caesarean Section Emergency No Senent-Boza 33 Spain All Emergency No Barret 34 Spain Burns Emergency No Hussain 35 London Cardiac Emergency No Li 36 China Thoracic Not stated No Case reports Gou, SM 37 China Pancreas Emergency Garcia-Portabella 38 Spain Ortho Emergency Davis-Sandfoss 39 USA Breast Cancer Elective Han 40 China Thoracic Emergency Lepre 41 Italy General Surgery Emergency Lyra 42 Portugal Obstetrics Elective Powezka 43 UK Vascular Emergency Qin 44 China Liver Transplant Emergency Rinaldi 45 Italy Vascular Emergency Stevenson 46 UK Ortho cancers Elective Sunkin 47 USA Orthopaedics Emergency Wen 48 China Neurosurgery Emergency Xuan 49 China Lung Transplant Emergency report on surgical outcomes; were incidence only studies, practice guidelines, consensus stateme...…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%